Multi-layer agility: a proposed concept of business agility in organizational behavior perspective - Nopriadi Saputra; Endang Chumaidah; Riza Aryanto (Diponegoro International Journal of Business, 2021)
Turbulence in the business environment imposed large companies or market leaders to become more agile in doing business. Developing business agility can be implemented in many levels of business organization. This paper proposes a multi-layer perspective of business agility construct by examining construct validity through structural equation modelling. Based on organizational behavior theory, this paper proposes combining construct from three different perspectives of business agility: strategic agility from an organizational perspective, leadership agility from a group perspective, and learning agility from an individual perspective. The paper involved 477 supervisors and managers of Indonesian oil palm plantations as respondents. The data was analyzed by using Lisrel version 9.30. The result explains that the second-order construct is the best-fit construct for defining multi-layer agility as a measurement model.